Specific gravity and fiber morphology of Kelempayan (Anthocephalus cheninsis) / Wan Muna Leza Wan Mohd Isa - Wan Mohd Isa, Wan Muna Leza (2003)
The study of Kelempayan (Anthocephalus chenisis) are about their specific gravity and fiber morphology. Kelempayan is from Rubiacea family and also pioneers species that have fast growing. From the study we can determine fiber length, cell wall thickness, runkle ratio, felting power, coefficient of suppleness, moisture content, specific gravity and relationship between moisture content and specific gravity at different level and portion. Felting power of Kelempayan species is 40 and runkle ratio is 1.77 in average. Fibers have different level and portion. Moisture content of Kelempayan is 150 % and specific gravity 0.39 in average.